The effect of cardiorespiratory fitness and physical activity levels on cognitive functions in survivors of childhood acute lymphoblastic leukemia. (2nd October 2020) - Gendron, Élisabelle; Caru, Maxime; Léveillé, Pauline; Sultan, Serge; Robaey, Philippe; Lemay, Valérie; Drouin, Simon; Bertout, Laurence; Andelfinger, Gregor; Krajinovic, Maja; Laverdière, Caroline; Sinnett, Daniel; et al.
Abstract: Introduction. Most childhood acute lymphoblastic leukemia (ALL) survivors develop chronic treatment-related adverse effects several years after the end of the treatment. Regular physical activity and a good cardiorespiratory fitness can decrease the risks of neurological disturbances and increase cognitive function scores. The aim of this study was to examine the effect of good cardiorespiratory fitness and physical activity levels on cognitive functions. Methods. We enrolled 219 survivors of childhood ALL. The participants underwent a cardiopulmonary exercise test, neuropsychological tests of executive functions (i.e. verbal fluency, cognitive flexibility, working memory, processing speed) and completed a physical activity questionnaire. We calculated the odds ratio to obtain the preventive fraction of physical activity and cardiorespiratory fitness levels on cognitive functions. Results . The cohort is 52% male and 48% female. A total of 182 survivors (83%) have a cardiorespiratory fitness below their predicted (<100%). Our analyses show that there is an association between good cardiorespiratory fitness and processing speed (preventive fraction of 70% for dominant hand (p < 0.01) and 65% for non-dominant hand (p < 0.01)) and with cognitive flexibility identified as the category switching measure of the D-KEFS verbal fluency (preventive fraction of 61%; p < 0.05). Conclusion . Good cardiorespiratory fitness and good levels of physical activity were associated to a preventive fraction for most cognitive function parameters measured. Good cardiorespiratory fitness levels were significantly associated with a lower prevalence of deficits in processing speed (i.e., dominant hand and non-dominant hand) and in cognitive flexibility (i.e., category switching) in childhood acute lymphoblastic leukemia survivors.